Arthropod-borne pathogens circulating in free-roaming domestic cats in a zoo environment in Brazil - Andre, Marcos Rogerio [UNESP]; Baccarim Denardi, Nathani Cristina [UNESP]; Marques de Sousa, Keyla Carstens [UNESP]; Goncalves, Luiz Ricardo [UNESP]; Henrique, Paloma Canedo; Grosse Rossi Ontivero, Claudia Regina; Lima Gonzalez, Irys Hany; Cabral Nery, Carolina Vaz; Fernandes Chagas, Carolina Romeiro; Monticelli, Caue; Gabriela Alexandre de Santis, Ana Claudia [UNESP]; Machado, Rosangela Zacarias [UNESP] (Elsevier B.V., 2014)
Recently, tick and flea-borne pathogens have been detected in wild carnivores maintained in captivity in Brazilian zoos. Since free-roaming cats are frequently found in Brazilian zoos, they could act as reservoirs for arthropod-borne pathogens, which could be transmitted to endangered wild carnivores maintained in captivity in these institutions. On the other hand, stray cats in zoos may play a role as sentinels to pathogens that circulate among wild animals in captivity. The present work aimed to detect the presence of Anaplasmataceae agents, hemoplasmas, Bartonella species, piroplasmas, and Hepatozoon sp. DNA in blood samples of 37 free-roaming cats in a Brazilian zoo. Three (8%) cats were positive for Anaplasma spp. closed related to Anaplasma phagocytophilum; 12 (32%) cats were positive for hemoplasmas [two (5%) for Mycoplasma haemofelis, five (13.5%) for Candidatus Mycoplasma haemominutum, and five (13.5%) for Candidatus Mycoplasma turicensis]; 11(30%) were positive for Bartonella spp., six (16%) were positive Babesia vogeli and one (3%) for Theileria sp. Coinfection with multiple arthropod-borne agentes was observed in sampled cats. None of sampled cats were positive for Ehrlichia spp., Cytauxzoon spp., or Hepatozoon spp. in PCR. This is the first molecular detection of Babesia vogeli and Theileria sp. in domestic cats in Brazil. The control of the population of free-roaming cats in these conservation institutions is much needed aiming to prevent the potential transmission to endangered wild animals maintained in captivity, such as wild neotropical wild felids, as well as to human beings visiting zoos. (C) 2014 Elsevier GmbH. All rights reserved.
Keywords: Anaplasmataceae; Bartonella spp.; Brazil; Cats; Piroplasms; Zoo